Incidence and perinatal outcome of multiple pregnancy in a tertiary care centre in Central India - Yadav, Nutan; Alwani, Madhuri; Singh, Ankita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The incidence of multiple pregnancy is increasing all over the world because of assisted reproductive technology or spontaneously as a result of numerous risk factors. The objective of this study was to study the perinatal outcome of multiple pregnancy in a tertiary care centre in central India Methods: It is a prospective study total 2289 pregnant woman were enrolled. Out of which 72 pregnant women were either a twin or triplet. 2217 pregnant women were singleton and had acted as controls. Perinatal outcomes including perinatal morbidity and mortality in relation to history regarding any complication in the present pregnancy were noted and analyzed. Results: In case of multiple pregnancy 90.2% were conceived between 20-30 years of age and 9.8% more than 30 years.13.9% cases of multiple pregnancy were less than 34 weeks at the time of delivery. The IUGR in multifetal pregnant patient was significantly higher. Oligohydromnios was seen in 3 out of 72 multifetal gestation which accounted for 4.1%. The proportion of singleton and multiple pregnant females who had anemia during pregnancy was 92.33% and 91.67%. Most common indication of LSCS in multifetal gestation is abnormal presentation during labour accounting for 41.7% of LSCS. The most common indication for NICU admission in case of multifetal pregnancy was 80.8%. Conclusions: Majority of the twin pregnancy is high risk one, and as such all twin preganancies should have mandatory hospital delivery. Early diagnosis, antenatal, intra-natal and post-partum cares are necessary to improve the outcome.